Diagnosis and management of Hodgkin lymphoma in children, adolescents, and young adults. Issue 1 (March 2023) - Belsky, Jennifer A.; Hochberg, Jessica; Giulino-Roth, Lisa
Abstract: Advances in the management of Hodgkin lymphoma in children, adolescents and young adult have resulted in survival outcomes exceeding 90%. The risk of late toxicity, however, remains a significant concern for survivors of HL and the focus of modern trials have been to advance cure rates while reducing long term toxicity. This has been accomplished through response-adapted treatment approaches and the incorporation of novel agents, many of which target the unique interaction between the Hodgkin and Reed Sternberg cells and the tumor microenvironment. In addition, an improved understanding of prognostic markers, risk stratification, and the biology of this entity in children and AYAs may allow us to further tailor therapy. This review focuses on the current management of HL in the upfront and relapsed settings, recent advances in novel agents that target HL and the tumor microenvironment, and promising prognostic markers that may help guide the future management of HL.